Towards a Linguistically-Oriented Textual Entailment Test-Suite for Polish Based on the Semantic Syntax Approach - Adam Przepiórkowski (Cognitive Studies | Études cognitives, 2015)
Towards a Linguistically-Oriented Textual Entailment Test-Suite for Polish Based on the Semantic Syntax Approach